Phenomenological model of effective viscosity of oil material during extrusion processing - A. V. Gukasyan (Новые технологии, 2019)
The aim of the research is to study the effective viscosity of oil-bearing material during the extraction process during extrusion processing of oil-bearing materials in the FP press. A phenomenological model of a layered flow has been used to describe the extrusion process and a flow balance model of filtration. As a result of the research, an estimation of the effective viscosity of the oil-bearing material in the process of changing the flow of oil-bearing material in the curb chamber on the flight screw of the oil-press unit has been obtained. An equation has been obtained that generalizes the well-known one-dimensional Poiseuille equation, the use of which allows us to determine the functional dependence of the volumetric flow rate of the structured Bingham body flow through the press outlet device, which significantly increases the accuracy of identifying the flow rheological parameters with known geometric parameters of the outlet device. A comparative analysis of alternative models of the flow of plastic mass during the extrusion transportation of oilseed materials has been carried out, which shows that the transition from a one-dimensional to a two-dimensional model significantly affects the determination of the capacity of the screw press channel of (extruder). The main conclusion is the need to use a theoretically based model of layered flow in the screw channel when describing the process of extracting vegetable oil. As a result, the pressures developed by the screw on the turns of the curb chamber under various operating conditions of the oil extraction unit have been determined.The possibility of using technological operating modes to predict the extraction of oil and pressure developed by the flight screw in the curb chamber is shown.